2017
DOI: 10.4172/2155-9929.1000359
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Sentinel Lymph Node Intraoperative Touch Imprint Cytology in Breast Cancer Surgery

Abstract: Background: One of the strongest prognostic factor for breast cancer is the regional lymph node status, which can be evaluated intraoperatively by sentinel lymph node biopsy. Many methods (e.g. frozen section, touch imprint cytology (TIC) and one-step nucleic-acid amplification) are available to detect metastatic cells in axillary lymph nodes. The aim of this study is to evaluate the feasibility of using TIC to detect metastatic cells in sentinel lymph nodes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
0
2
1
Order By: Relevance
“…In contrast to our results, Motomura et al reported that TIC was better than FSA 21 . Lacuzzo et al also demonstrated similar results and reported that TIC was a reliable and fast technique for identifying intraoperative SLN metastasis 22 . They showed that TIC had lower sensitivity but much greater specificity, which is not in agreement with our findings 22 .…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to our results, Motomura et al reported that TIC was better than FSA 21 . Lacuzzo et al also demonstrated similar results and reported that TIC was a reliable and fast technique for identifying intraoperative SLN metastasis 22 . They showed that TIC had lower sensitivity but much greater specificity, which is not in agreement with our findings 22 .…”
Section: Discussioncontrasting
confidence: 99%
“…Lacuzzo et al also demonstrated similar results and reported that TIC was a reliable and fast technique for identifying intraoperative SLN metastasis 22 . They showed that TIC had lower sensitivity but much greater specificity, which is not in agreement with our findings 22 . Russo et al demonstrated that FSA had an acceptable false‐negative rate during SLN biopsy 23 .…”
Section: Discussionmentioning
confidence: 41%
“…It has been widely used in cervical and anal cancer screening programs, which have achieved a great reduction in its incidence in many countries [ 25 , 26 ]. This simple morphology-based diagnostic method is routinely used in clinical practice for the diagnosis, decision-making, and treatment of benign and malignant conditions, either alone or complementary to standard surgical pathology diagnosis [ 27 , 28 , 29 ]. Diagnostic cytology has many advantages, such as being a simpler and less-invasive procedure than biopsy or surgical resection.…”
Section: Introductionmentioning
confidence: 99%